Immunopathogenesis and detection methods of type 2 diabetes - Li, Yiwei (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Diabetes is a disease that is increasingly prevalent on a global scale. Type 2 diabetes (T2D) accounts for 90% of all diabetes cases and is a chronic condition primarily influenced by factors such as obesity and genetics. This condition often leads to the development of various cardiovascular diseases. A diverse of different detection methods for the T2D have been developed and achieved good detection and analysis results. In addition, numerous studies have indicated a close connection between T2D and immune inflammation. This research primarily introduces the current status of diabetes, provides a detailed summary of the connection betweenT2D and the immune system, and presents novel immune biomarkers related to T2D. Some new immunological testing methods will be analyzed in this research. In the future, there is hope that these new biomarkers can be used to design more advantageous therapeutic drugs for diabetes patients and more convenient, sensitive, and low-cost detection methods.